Legal and economic aspects of money laundering in selected EU member states - Brzezińska, Joanna (Prawne i ekonomiczne aspekty przestępstwa prania brudnych pieniędzy w wybranych państwach Unii Europejskiej, 2020)
The main purpose of the article is to draw attention to the nature and structure of the legal regulations, the essence of which is combating money laundering in selected European Union states (France and Belgium). Therefore, the provisions included in the Penal Codes (art. 324 – 1 of the French Penal Code and art. 505 of the Belgian Penal Code), the basic purpose of which is combating the discussed pathology occurring in the indicated European member states, are presented. The omissions and legal gaps of the regulations referred to above, which should be eliminated by the European legislators in order to ensure a higher level of safety in the functioning of the financial markets and minimise the frequency of specified crime are also highlighted. Moreover, the range of individual sanctions penalising the crime of money laundering in France and Belgium were analysed. The second area of considerations was the analysis of the statistical data relating to the level of suspicious declarations performed by specific entities (e.g. banks, credit institutions, exchange offices, insurance companies, brokerage houses, investment and financial enterprises) in the determined states on individual stages of money laundering realisation (placement, layering and integration). These transactions are mainly aimed at hiding and distributing the financial means of illegal origin, and the determination of their frequency which will support the estimation of the scale of the analysed pathology in individual EU member states
Ekonomia XXI Wieku = Economics of the 21st Century, 2020, Nr 23, s. 45-55